Complementarities and competition: Unpacking the drivers of entrants' technology choices in the solar photovoltaic industry - Kapoor, Rahul; Furr, Nathan R. (Strategic Management Journal, 2015)
Entrants in new industries pursue distinct technologies in hopes of winning the technology competition and achieving sustainable competitive advantage. We draw on the complementary assets framework to predict entrants' technology choices in an emerging industry. Evidence from the global solar photovoltaic industry supports our arguments that entrants are more likely to choose technologies with higher technical performance and for which key complementary assets are available in the ecosystem. However, diversifying entrants are more likely to trade off superior performance for complementary asset availability whereas start‐up entrants are more likely to trade off complementary asset availability for superior performance. This difference is largely due to diversifying entrants with pre‐entry capabilities related to the industry. The study offers a novel illustration of how complementarities and competition shape entry strategies . Copyright © 2013 John Wiley & Sons, Ltd.